The Silmarillion - Tolkien, J. R. R. (John Ronald Reuel), 1892-1973.; Harper Collins (London : HarperCollins, 1999)
Presents the history of the rebellion of Feanor, most gifted of the Elves, against the gods, his exile from Valinor, and return to Middle-earth.
Includes a fold out map.
Includes index.
Keywords: Middle Earth (Imaginary place) -- Fiction; Fantastic fiction